2017
DOI: 10.1371/journal.pone.0180258
|View full text |Cite
|
Sign up to set email alerts
|

RBM10 promotes transformation-associated processes in small cell lung cancer and is directly regulated by RBM5

Abstract: Lung cancers are the leading cause of cancer-related deaths worldwide, with small cell lung cancer (SCLC) being the most aggressive type. At the time of diagnosis, SCLC has usually already metastasized, and an astonishing 95% of patients eventually succumb to the disease. This highlights the need for more effective SCLC screening and treatment options. Interestingly, the earliest and most frequent genetic alteration associated with lung cancers involves a lesion in the region to which the RNA binding protein R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 78 publications
1
56
0
Order By: Relevance
“…As the GLC20 cells used in this study almost exclusively expressed RBM10v1 at the protein level, it was most likely RBM10v1 that was interacting with the RBM10v2 RNA. Strikingly, although RBM10v1 protein levels were substantially higher than RBM10v2 protein levels, mRNA expression levels of RBM10v1 and RBM10v2 were very similar, suggesting that the interaction of RBM10v1 protein with RBM10v2 RNA is integral to an RBM10 translational self‐regulation mechanism, at least in GLC20 cells . Of note, in the study by Sun et al described above, RBM10v1 overexpression was followed by decreased RBM10v2 expression at both the mRNA and protein levels, suggesting that multiple levels of RBM10 self‐regulation exist in HEK293 cells.…”
Section: Regulation Of Rbm10mentioning
confidence: 86%
See 4 more Smart Citations
“…As the GLC20 cells used in this study almost exclusively expressed RBM10v1 at the protein level, it was most likely RBM10v1 that was interacting with the RBM10v2 RNA. Strikingly, although RBM10v1 protein levels were substantially higher than RBM10v2 protein levels, mRNA expression levels of RBM10v1 and RBM10v2 were very similar, suggesting that the interaction of RBM10v1 protein with RBM10v2 RNA is integral to an RBM10 translational self‐regulation mechanism, at least in GLC20 cells . Of note, in the study by Sun et al described above, RBM10v1 overexpression was followed by decreased RBM10v2 expression at both the mRNA and protein levels, suggesting that multiple levels of RBM10 self‐regulation exist in HEK293 cells.…”
Section: Regulation Of Rbm10mentioning
confidence: 86%
“…Interestingly, an earlier manuscript by Bechara et al showed that mutation of this alternatively spliced valine residue to glutamic acid did alter RBM10 function, supporting the notion that the alternative splicing of this codon could have functional implications for RBM10. In addition, our group recently showed that RBM5 can distinguish between these +/− GTG RBM10 splice variants; RBM5 specifically bound only RBM10v2(V277del) . Taken together, these results suggest that the alternative splicing of RBM10 results in changes in protein tertiary structure that either directly (eg, +/− valine in the RRM domain) or indirectly (eg, RBM10v1 versus RBM10v2) influence function.…”
Section: Regulation Of Rbm10mentioning
confidence: 88%
See 3 more Smart Citations